DIGI-FC-SML: enhancing soil mechanics laboratory learning with interactive flashcards - Alias, Asmidar; Ariffin, Kamisah; Mohd Noor, Nur Asmaliza (2025)
The Soil Mechanics Laboratory course involves numerous technical terms and detailed explanations that demand both memorization and conceptual understanding. Understanding soil laboratory experiments is fundamental for civil and geotechnical engineering students, however, traditional learning methods often lack engagement and efficiency. The Digital Flash Card for Soil Mechanics Laboratory (DIGI-FC-SML) is an innovative educational tool which is interactive online flashcards designed specifically for soil laboratory experiments. The flashcards cover key aspects of each experiment: including the objective, required apparatus, procedure, and expected results. The tool leverages proven learning techniques such as spaced repetition, gamification, and microlearning to boost comprehension and retention. It is grounded in the learning theory that complex subjects are best mastered through intensive, consistent and structured study. With a user-friendly interface and gamebased modes, students can learn anytime, anywhere, at their own pace. Students can self-assess their understanding through engaging and practical quizzes provided at the end of each topic, with the content freely accessible on quizlet.com. The flashcards aim to transform technical content into manageable, interactive sessions that support both exam preparation and conceptual understanding. This digital approach offers a scalable, cost-effective solution to enhance laboratory learning experiences, making soil laboratories more accessible, engaging, and effective for the next generation of engineers. Moreover, DIGI-FC is a versatile tool that can be easily adapted and expanded into a series of learning resources for other subject areas.